Tratamento do Retinoblastoma Avançado - Sá, Geraldo de Matos de (2023)
Thirty six cases of retinoblastoma are studied all of them belonging to stages III and IV. The authors analysed the treatment selected, as well as the correct management of drugs, complications and the results: there were 38,8% of the whole number of patients alive at least 3 years after treatment, and 27,7% living for more than 5 years since therapy began.